Experimental pigeon paramyxovirus-1 infection in chicken: evaluation of infectivity, clinical and pathological manifestations and diagnostic methods. (10th January 2020) - Hüppi, Linda; Ruggli, Nicolas; Python, Sylvie; Hoop, Richard; Albini, Sarah; Grund, Christian; Vögtlin, Andrea
Abstract : Several pigeon paramyxovirus-1 (PPMV-1) outbreaks in feral pigeons were described recently in Switzerland. The potential of PPMV-1 to induce the notifiable Newcastle disease in chickens is discussed controversially. Therefore, in order to study epidemiologically relevant parameters such as the kinetics of PPMV-1 replication and shedding as well as seroconversion after infection, chickens were infected experimentally with a Swiss PPMV-1 isolate. This generated also defined sample material for the comparison of diagnostic tests. The infectivity of the Swiss PPMV-1 isolate for chickens was demonstrated successfully by virus shedding after experimental inoculation. Our data suggest that long-lasting shedding for up to 60 days can occur in chickens infected with PPMV-1. The isolate used here was of low pathogenicity for chickens. Different quantitative reverse transcription PCR assays were evaluated with a set of Swiss PPMV-1 isolates, and various samples from experimentally infected chickens were analysed with respect to their suitability for viral RNA detection. At 14 days post-infection, virus genome was detected mainly in spleen, caecal tonsils, heart, cloacal swabs, liver, proventriculus, duodenum and kidney tissue samples. Overall, the level of virus replication was low. Not all assays used routinely in diagnostics were capable of detecting viral genome from the isolates tested. Possible explanations are the genetic divergence of PPMV-1 and the low level of viral RNA in the samples. In contrast, two methods that are not used routinely proved more suitable for virus-genome detection. Importantly, the collection of material from various different organs is recommended, in addition to the kidney and brain analysed routinely. In conclusion, this study shows that there is a need to reconsider the type of samples and the protocols used for the detection of PPMV-1 RNA in chickens.